Molecular and cellular basis of embryonic cardiac chamber maturation. (October 2021) - Dong, Yanhan; Qian, Li; Liu, Jiandong
Abstract: Heart malformation is the leading cause of human birth defects, and many of the congenital heart diseases (CHDs) originate from genetic defects that impact cardiac development and maturation. During development, the vertebrate heart undergoes a series of complex morphogenetic processes that increase its ability to pump blood. One of these processes leads to the formation of the sheet-like muscular projections called trabeculae. Trabeculae increase cardiac output and permit nutrition and oxygen uptake in the embryonic myocardium prior to coronary vascularization without increasing heart size. Cardiac trabeculation is also crucial for the development of the intraventricular fast conduction system. Alterations in cardiac trabecular development can manifest as a variety of congenital defects such as left ventricular noncompaction. In this review, we discuss the latest advances in understanding the molecular and cellular mechanisms underlying cardiac trabecular development.